STUDI ANALISIS KETIDAKSEIMBANGAN BEBAN GARDU DISTRIBUSI MF0001 PADA ULP KERSIK TUO TERHADAP RUGI-RUGI DAYA AKIBAT ARUS NETRAL DAN SUHU - Haris Syaifullah; Arfita Yuana Dewi Rachman; Zuriman Anthony; Sepannur Bandri; Zulkarnaini (PT. Hasba Edukasi Mandiri, 2026)
This study focuses on analyzing the impact of load imbalance on the MF0001 distribution transformer at PT PLN (Persero) ULP Kersik Tuo, particularly focusing on power losses caused by neutral current and temperature rise. Load imbalance occurs when the current distributed across the three phases is not equal, resulting in the flow of neutral current. This neutral current contributes to significant power losses and causes an increase in temperature at critical connection points, which may lead to accelerated damage to distribution equipment. Measurement data showed that the current in phases R, S, and T were 226 A, 156 A, and 135 A respectively, while the neutral current reached 104 A. The hotspot temperature on phase R was recorded at 105°C, which exceeds the standard operational temperature limit for transformers. To address this issue, load balancing was carried out by shifting loads from overloaded phases to underloaded ones. After balancing, there was a significant decrease in both neutral current and temperature. The power losses were reduced from 11% to below the threshold set by the SPLN 1997 standard, which is 2%. The results of this study demonstrate that load balancing is an effective technical solution to improve energy efficiency, reduce overheating risks, and minimize power losses in low-voltage distribution systems.